Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1055/s-0036-1588783
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal-Catalyzed Synthesis of Spirolactones

Abstract: Spiranoid lactone structures can frequently be observed as scaffold segments of various biochemical compounds and drugs of natural origin. Examples of these structures have been identified among terpenoids, alkaloids, steroids, carbohydrates, and many other natural products. Such a broad natural diversity and biological activity allows a wide spectrum of these systems to be attractive targets for synthetic and medicinal chemists. Covering a broad spectrum of recognized approaches toward the design of spirolact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The spirobutyrolactone moiety also is the core framework of many natural products and bioactive molecules (Scheme 1). 9 To further expand the stereochemical and skeletal diversity of natural product harmaline-based hybrids, we then employed 3-isothiocyanato butyrolactone 2 to serve as a useful building block in this reaction with harmaline or its derivative for the construction of potentially bioactive structural spiropentacyclic harmaline–butyrolactone hybrids 3 having significant molecular complexity. To our delight, this formal [3+2] cycloadditions also proceeded smoothly to afford the desired products 3ia–ka in 88–90% yields with 8 : 1–20 : 1 dr ( 3ia–ka , Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…The spirobutyrolactone moiety also is the core framework of many natural products and bioactive molecules (Scheme 1). 9 To further expand the stereochemical and skeletal diversity of natural product harmaline-based hybrids, we then employed 3-isothiocyanato butyrolactone 2 to serve as a useful building block in this reaction with harmaline or its derivative for the construction of potentially bioactive structural spiropentacyclic harmaline–butyrolactone hybrids 3 having significant molecular complexity. To our delight, this formal [3+2] cycloadditions also proceeded smoothly to afford the desired products 3ia–ka in 88–90% yields with 8 : 1–20 : 1 dr ( 3ia–ka , Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…Skeletal construction is an important method in synthetic communities for the rapid and reliable construction of core frameworks with various functional groups. In 2018, Guo et al [92] developed a new and promising Michael-initiated Pinnick oxidative spirolactonization reaction for the synthesis of potentially bioactive chiral spirocyclic oxindole-lactone derivatives 68 in up to 97% yield with up to 99% ee [ Scheme 35,top]. The corresponding products 68 contain spirocyclic oxindole-paraconic esters and bear three chiral stereocenters.…”
Section: Spirolactonization Reaction Of 3-olefinic Oxindolesmentioning
confidence: 99%
“…3-Olefinic oxindoles as lactone construction reagents 66 in Michael-initiated Pinnick oxidative spirolactonization reactions. This figure is used with permission from the American Chemical Society [92] . Scheme 36.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…It is important to address this type of equilibrium, as natural cyclocalopins possess not only a 2α-hydroxy configuration (e.g., cyclocalopin A and C) but also 2β-hydroxy analogues (e.g., cyclocalopin E and cyclopinol) . It was envisioned that the bis-γ,δ-lactone system 2 as a key intermediate could be rapidly established by a direct or stepwise cyclocarbonylation of newly introduced allenyl glyoxylate 4 through a [2 + 2 + 1]-cycloaddition . A crucial aspect of our design was the potential to concisely access a tricyclic skeleton 1 for cyclocalopin A with proper stereoselections from allenyl alcohol 5 within six to eight steps.…”
mentioning
confidence: 99%
“…Our investigations began with allenyl glyoxylate 4 to validate the feasibility as a substrate for the synthesis of the bis-γ,δ-lactone 2 through a [2 + 2 + 1]-cycloaddition. Initial attempts for direct cyclocabonylation of the allenyl glyoxylate 4 through three-component assembly indicated that conversion to the adduct α-methylene bis-γ,δ-lactone 2 could not be realized with several catalytic systems previously employed conditions for similar systems. , This insufficient reactivity could be interpreted by assuming that the electron deficiency of the glyoxyl moiety disrupted the formation of the intermediate model A (Scheme ). After surveying numerous conditions, the desired bislactone 2 was produced as a single adduct with the use of stoichiometric Mo­(CO) 6 (conditions A, Scheme ) or catalytic Ru 3 (CO) 12 under CO atmosphere (conditions B, Scheme ).…”
mentioning
confidence: 99%